2016
DOI: 10.5812/iranjradiol.26806
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reconstruction Methods in a Small Animal Cardiac Positron Emission Tomography Study Using a 18F-Labeled Myocardial Agent, [18F] FPTP

Abstract: Background: Reconstruction of positron emission tomography (PET) imagery is essential for accurate diagnosis in nuclear medicine. Thus, several image reconstruction methods were developed to enhance image quality and accuracy. Objectives: We performed PET studies using a new myocardial imaging agent, (5-[18 F] fluoropentyl) triphenylphosphonium cation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Sondergaard HM et al reported that the OSEM reconstruction method produced better image quality and less noise than the FBP reconstruction method [16]. HS Kim et al compared reconstruction methods (FBP, OSEM2D, OSEM3D, and 3DRP) in cardiac PET imaging and reported that the OSEM3D reconstruction method showed a higher correlation with TTC staining and provided better image quality and contrast than other methods [17]. Post-filtering produces blurred images but can reduce the image noise.…”
Section: Introductionmentioning
confidence: 99%
“…Sondergaard HM et al reported that the OSEM reconstruction method produced better image quality and less noise than the FBP reconstruction method [16]. HS Kim et al compared reconstruction methods (FBP, OSEM2D, OSEM3D, and 3DRP) in cardiac PET imaging and reported that the OSEM3D reconstruction method showed a higher correlation with TTC staining and provided better image quality and contrast than other methods [17]. Post-filtering produces blurred images but can reduce the image noise.…”
Section: Introductionmentioning
confidence: 99%